"Two‐Point" Self‐Assembly and Photoinduced Electron Transfer in meso‐Donor‐Carrying Bis(styryl crown ether)‐BODIPY–Bis(alkylammonium)fullerene Donor–Acceptor Conjugates1. Issue 17 (9th August 2017) - Shao, Shuai; Gobeze, Habtom B.; Karr, Paul A.; D'Souza, Francis
Abstract: BF2 ‐chelated dipyrromethene, BODIPY, was functionalized to carry two styryl crown ether tails and a secondary electron donor at the meso position. By using a "two‐point" self‐assembly strategy, a bis‐alkylammonium‐functionalized fullerene (C60 ) was allowed to self‐assemble the crown ether voids of BODIPY to obtain multimodular donor–acceptor conjugates. As a consequence of the two‐point binding, the 1:1 stoichiometric complexes formed yielded complexes of higher stability in which fluorescence of BODIPY was found to be quenched; this suggested the occurrence of excited‐state processes. The geometry and electronic structure of the self‐assembled complexes were derived from B3LYP/3‐21G(*) methods in which no steric constraints between the entities was observed. An energy‐level diagram was established by using spectral, electrochemical, and computational results to help understand the mechanistic details of excited‐state processes originating from 1 bis‐styryl‐BODIPY*. Femtosecond transient absorbance studies were indicative of the formation of an exciplex state prior to the charge‐separation process to yield a bis‐styryl‐BODIPY . + –C60 . − radical ion pair. The time constants for charge separation were generally lower than charge‐recombination processes. The present studies bring out the importance of multimode binding strategies to obtain stable self‐assembled donor–acceptor conjugates capable of undergoing photoinduced charge separation needed in artificial photosynthetic applications. Abstract : Shining light on the matter : Formation of stable self‐assembled hybrids and the occurrence of photoinduced electron transfer via an intermediate exciplex state in bis(styryl crown ether)‐BODIPY–fullerene donor–acceptor conjugates is demonstrated (see figure).